The Intimate Partner Violence Stigmatization Model and Barriers to Help Seeking - Overstreet, Nicole M.; Quinn, Diane M. (Basic and applied social psychology, 2013)
The intimate partner violence (IPV) stigmatization model identifies how three stigma components hinder IPV help-seeking behaviors: cultural stigma, stigma internalization, and anticipated stigma. Cultural stigma highlights societal beliefs that delegitimize people experiencing abuse. Stigma internalization involves the extent to which people come to believe that the negative stereotypes about those who experience IPV may be true of themselves. Anticipated stigma emphasizes concern about what will happen once others know about the partner abuse (e.g., rejection). We provide an integrative literature review that supports the IPV stigmatization model and its role in reducing help-seeking behaviors.